Street Businesses in Addis Ababa: Causes, Consequences and Administrative Interventions (Journal of Governance and Development (JGD), 2020)
Street vending has long been a source of debate among development economists. It has been argued that direct government intervention that aids this sector will encourage rural to urban migration. Others have argued that this sector deserves government help as often more than 50% of the urban labour force is employed by this sector. This study is designed to assess the causes, consequences and administrative interventions of street vending in Addis Ababa with particular reference to Yeka sub-city. Data were collected from randomly selected samples of 330 street vendors, 14 code enforcers and 9 government officials through questionnaires and interview of key respondents. The finding shows most of the traders came from outside Addis Ababa in search of jobs. Street vending proliferated as a way of life and a coping mechanism adopted by those economically under privileged segment of the society. Factors that led to street vending were complex and varied. According to the findings, absence of opportunity in the formal sector was the main factor that led the operators to street vending. This is followed by the need to support their family and themselves. The authorities stated that unless managed well street vending will have negative impact on traffic movement, encroach on public space and create unfair completion with formal businesses. To mitigate these problems the city administration has issued street vending regulation No. 5 in 2018 so that specific vending plots are allocated and the vendors need to do their business legally and those who fail to follow the rules will be dealt with by the law.